Non-signaling but all important: how the linker, hinge, and transmembrane domains in the CAR hold it all together - Bernard, Grace; Evgin, Laura (Frontiers in Immunology, 2025)
The chimeric antigen receptor (CAR) is a synthetic and modular molecule composed of both signaling and non-signaling domains that allows a T cell to recognize cell surface antigens and trigger cytolytic functionality. It is appreciated that the non-signaling structural components, including the linker, hinge, and transmembrane domains, can dramatically alter how the CAR molecule interacts with itself and other endogenous molecules in the immune synapse. Herein, we describe the current understanding of how the structural domains can alter CAR T cell therapeutic efficacy and highlight how knowledge of the target antigen characteristics can inform CAR design choices.